Volume 1: Symposia, Parts a and B 2008
DOI: 10.1115/fedsm2008-55132
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Stall Behavior in a Diffuser of Mixed Flow Pump and Its Suppression

Abstract: The relationship between pump characteristic instability and internal flow was investigated on a mixed flow pump with specific speed ωs = 1.72 (dimensionless) or 700 (m3/min, m, min−1) by using a commercial CFD code and a dynamic PIV (DPIV) measurement. As a result, it was clarified that the diffuser rotating stalls causes the positive slope of a head-flow characteristic and the backflow at hub-side of the vaned diffuser plays an important role on the onset of the diffuser rotating stall. The complex behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To suppress the rotating stall in the diffuser, Miyabe et al enlarged the diameter of the hub at the diffuser inlet and placed a swirl stop at the pump entrance. The positive slope of the head-flow performance still occurred at partial flow rate [16]. Figure 10, which is compared with the numerical simulation result of a conventional pump.…”
Section: Factors For the Abrupt Head Dropmentioning
confidence: 89%
See 1 more Smart Citation
“…To suppress the rotating stall in the diffuser, Miyabe et al enlarged the diameter of the hub at the diffuser inlet and placed a swirl stop at the pump entrance. The positive slope of the head-flow performance still occurred at partial flow rate [16]. Figure 10, which is compared with the numerical simulation result of a conventional pump.…”
Section: Factors For the Abrupt Head Dropmentioning
confidence: 89%
“…He concluded that a rotating stall is flow instability caused by a positive slope of the head-flow rate performance curve, whereby the rotational frequency of rotating stall depends on the performance and the geometry of the rotor. Miyabe et al visualized the unsteady internal flow in diffuser with Dynamic PIV [15,16]. The authors clarified that the diffuser rotating stall causes the positive slope of a head-flow characteristic, and the backflow (i.e., a stall cell or a vortex) at the hub side of the diffuser plays an important role in the onset of a diffuser rotating stall.…”
Section: Review Of Rotating Stall In Pumpsmentioning
confidence: 99%
“…Miyabe et al. 25,26 used dynamic PIV technology to test and measure a mixed-flow pump, and found that the backflow in the guide vane played a crucial role in the occurrence of stall, and stall always occurred along with the decrease of flow rate. Zhu 27 found that the low momentum region near the suction side of the blade grows upstream as the flow rate decreases, resulting in a smaller stall margin for mixed-flow compressors, and that two different forms of tip leakage are the main cause of the low momentum region.…”
Section: Introductionmentioning
confidence: 99%
“…Energy performance and flow patterns of a mixed-flow pump with different tip clearances were investigated by Hao et al 7 and Liu et al, 8 based on which the influence of blade rotational angle and T-shape tip clearance was also studied. 9,10 DPIV was employed by Miyabe et al [11][12][13][14][15][16] to illustrate the inner flow of the vane. It was found that the periodic backflow at the inlet of guide vane under the low flow condition is one of the reasons for the positive slope of the performance curve.…”
Section: Introductionmentioning
confidence: 99%